Angola : 2007 Article IV Consultation; Staff Report; Staff Supplement and Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the 2007 Article IV Consultation on Angola highlights economic performance, macroeconomic stability, and fiscal policy. Growth in the medium term will rely increasingly on the non-oil sector, where reforms to promote private sector development will be critical to offset a potential loss in competitiveness from an appreciating real exchange rate. A key challenge is to ensure that political pressure to scale up public spending does not undermine macroeconomic stability. Lower output growth and oil revenues than envisaged in the baseline scenario could jeopardize public and external debt sustainability.